The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/cts.12905
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Green Tea Catechin Ingestion on the Pharmacokinetics of Lisinopril in Healthy Volunteers

Abstract: Lisinopril, a highly hydrophilic long‐acting angiotensin‐converting enzyme inhibitor, is frequently prescribed for the treatment of hypertension and congestive heart failure. Green tea consumption may reduce the risk of cardiovascular outcomes and total mortality, whereas green tea or its catechin components has been reported to decrease plasma concentrations of a hydrophilic β blocker, nadolol, in humans. The aim of this study was to evaluate possible effects of green tea extract (GTE) on the lisinopril pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…Drug concentrations of elderly patients (> 65 years) have been reported to be approximately double those of younger patients [ 28 ]. And a recent study demonstrated that a concomitant ingestion of epigallocatechin gallate (EGCG)-concentrated green tea extract significantly decreased lisinopril C max , AUC 0-24 and AUC 0-∞ by 71%, 69% and 67%, without altering renal clearance of Lisinopril [ 29 ]. However, in the present study, the enrolled subjects was all between 18 and 50 years old, and those who have drink too much tea were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Drug concentrations of elderly patients (> 65 years) have been reported to be approximately double those of younger patients [ 28 ]. And a recent study demonstrated that a concomitant ingestion of epigallocatechin gallate (EGCG)-concentrated green tea extract significantly decreased lisinopril C max , AUC 0-24 and AUC 0-∞ by 71%, 69% and 67%, without altering renal clearance of Lisinopril [ 29 ]. However, in the present study, the enrolled subjects was all between 18 and 50 years old, and those who have drink too much tea were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, whereas fexofenadine is mainly eliminated by hepato‐biliary elimination, pseudoephedrine is mostly excreted into urine. Previous clinical studies imply that GT and its main component, EGCG, may reduce the intestinal absorption of hydrophilic drugs with a relatively low bioavailability, including nadolol and lisinopril 2–4 . Therefore, taken together with data showing that GTE did not alter the apparent t 1/2 of fexofenadine, it is suggested that EGCG in the GTE mainly inhibits the intestinal absorption of fexofenadine.…”
Section: Discussionmentioning
confidence: 96%
“…Green tea (GT; Camellia sinensis ) and its main components, catechins, are perpetrators of clinically relevant food‐drug interactions with hydrophilic and nonmetabolized drugs, such as nadolol and lisinopril 1–4 . Among naturally occurring catechins, (−)‐epigallocatechin gallate (EGCG) plays a major role in GT–drug interactions 2,4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Common mechanisms include induction or inhibition of drug metabolizing enzymes, particularly the cytochrome P450s (CYPs), and transporters. Regarding transporters, studies showed green tea to decrease systemic area under the plasma concentration versus time curve (AUC) to the minimally metabolized drugs digoxin, fexofenadine, lisinopril, and nadolol 8–12 . These observations were attributed to inhibition of an intestinal uptake transporter(s) by green tea.…”
Section: Introductionmentioning
confidence: 99%